Extended Molecular Profiling Improves Stratification and Prediction of Survival After Resection of Colorectal Liver Metastases. Issue 5 (November 2019) - Lang, Hauke; Baumgart, Janine; Heinrich, Stefan; Tripke, Verena; Passalaqua, Monia; Maderer, Annett; Galle, Peter R.; Roth, Wilfried; Kloth, Michael; Moehler, Markus
Abstract : Objective: The aim of this study was to assess the effect of cancer-related genes and their mutations analyzed by next-generation sequencing (NGS) on the oncological outcome after resection of colorectal liver metastases (CRLM). Background: Traditional prognostic scores include clinical and pathological parameters of primary tumor and metastases. The modified clinical risk score (m-CS), based on size of metastases, primary tumor nodal status, and RAS mutation status outperformed traditional scores. We hypothesized to further improve the scoring system based on the results of NGS. Methods: Cancer tissues of 139 patients with CRLM were used for NGS. The work-up included the analysis of recurrent somatic mutations and copy number changes of 720 genes. Clinical data were extracted from a prospectively collected institutional liver database. Results: Depending on significance, the following cancer-related genes and their alterations (%) were further investigated: APC (86%), TP53 (78%), KRAS (29%), SMAD4 (15%), PIK3CA (14%), BRAF (8%), ERBB2 (6%), SMAD3 (5%), SMAD2 (4%), and NRAS (4%). The most predictive parameters for poor oncological outcome were alterations in the SMAD family ( P = 0.0186) and RAS-RAF pathway ( P = 0.032). Refining the m-CS by replacing RAS with RAS-RAF pathway and adding SMAD family resulted in an extended clinical risk score which is highly predictive for oncological outcome ( P < 0.0001). Conclusion: In conclusion, mutations of the SMAD family revealed a strong prognostic effect after surgery for CRLM. Integration of alterations of the SMAD family as well as the RAS/RAF pathway resulted in a new, still simple but highly prognostic score. Abstract : Supplemental Digital Content is available in the text